Influence of Traction Battery Arrangement on Risk of Thermal Runaway and Loads Suffered by Electric Vehicle Occupant during Side Collision - Ana Olona; Luis Castejón; David Valladares (Energies, 2023)
In the current electric vehicles, the purpose of the traction battery is to store energy. When designing this battery, different parameters are considered to arrange the battery/module/cells in the mechanically and thermally safest configuration. Moreover, the battery layout must produce correct dynamic behavior during collisions. In the present study, different battery configurations plus added energy absorbers were analyzed. To achieve this, an internal combustion vehicle modeled with finite elements was applied as the reference model. The structural behavior of the different battery configurations in the event of a side collision was examined. First, the safest arrangement was established with respect to both cabin intrusion and thermal runaway propagation. Second, the safest arrangement that guarantees the safety of the occupants in the event of a side collision was analyzed using MADYMO. This software includes experimentally validated dummies that allow insight into the stresses experienced by occupants. The results of the analysis showed that battery pack inclusion in the vehicle increases the stiffness of the car floor, resulting in fewer intrusions into the passenger compartment. Therefore, safety of the occupants is increased. However, none of the configurations analyzed showed sufficient safety against thermal runaway. This study contains sufficient contributions to the new body of knowledge, since there is no study that analyzes the safest configuration in terms of battery behavior with respect to intrusion into the passenger compartment and the effect of thermal runaway, together with the fact that this is the safest configuration for occupants after analyzing the injuries they experience in a side collision for the different configurations.